2022
DOI: 10.1021/acssuschemeng.2c02169
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Breakdown of a Membraneless Hydrogen–Bromine Redox Flow Battery

Abstract: A key bottleneck to society’s transition to renewable energy is the lack of cost-effective energy storage systems. Hydrogen–bromine redox flow batteries are seen as a promising solution, due to the use of low-cost reactants and highly conductive electrolytes, but market penetration is prevented due to high capital costs, for example due to costly membranes to prevent bromine crossover. Membraneless hydrogen–bromine cells relying on colaminar flows have thus been investigated, showing high power density nearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…This was also seen in optimistic calculations of cell and electrode ASR by Milshtein et al, showing the porous electrodes dominated cell resistance by contributing ∼150 mΩ·cm 2 each . This was further confirmed by Alfisi et al via a detailed resistance breakdown in a membraneless hydrogen–bromine cell, where it was found that the porous positive (bromine) electrode contributed ∼60% of the total cell ASR . The latter work also found only a small contribution (<10%) of the negative (hydrogen) electrode to cell ASR.…”
Section: High-power Batteries With Low Ocv (<13 V)supporting
confidence: 61%
See 4 more Smart Citations
“…This was also seen in optimistic calculations of cell and electrode ASR by Milshtein et al, showing the porous electrodes dominated cell resistance by contributing ∼150 mΩ·cm 2 each . This was further confirmed by Alfisi et al via a detailed resistance breakdown in a membraneless hydrogen–bromine cell, where it was found that the porous positive (bromine) electrode contributed ∼60% of the total cell ASR . The latter work also found only a small contribution (<10%) of the negative (hydrogen) electrode to cell ASR.…”
Section: High-power Batteries With Low Ocv (<13 V)supporting
confidence: 61%
“…Thus, breakthrough work for achieving yet higher power density may rest on reducing porous electrode ASR via either improved ion transport or catalytic capability. Both Chen et al and Alfisi et al identified that the largest contribution to losses in a porous bromine electrode were Faradaic losses due to electron transport across the solid–liquid interface, accounting for ∼50% of the electrode’s ASR in both works. , Thus, one promising strategy is to improve the catalytic capability of the porous electrode via, for example, doping or surface chemistry modifications.…”
Section: High-power Batteries With Low Ocv (<13 V)mentioning
confidence: 99%
See 3 more Smart Citations